Awareness, Knowledge, and Perceptions Regarding Rabies Prevention Among Rural Communities in Masaka District, Central Uganda: A Qualitative Study - Kankya, Clovice; Dürr, Salome; Hartnack, Sonja; Warembourg, Charlotte; Okello, Justine; Muleme, James; Okello, Walter; Methodius, Tubihemukama; Alobo, Grace; Odoch, Terence (Frontiers in Veterinary Science, 2022)
Rabies is a zoonotic disease that is mainly transmitted to humans through dog bites. It remains a major public health threat in many Asian and African countries, including Uganda. The main objective of this study was to investigate awareness, knowledge and perceptions of communities towards human and dog health related to rabies prevention, as well as dog management practices within Masaka district, central Uganda. Data collection involved nine key informant interviews (KII) and six focus group discussions (FGD). Methods used during focus group discussions included qualitative interviews (using open-ended questions), simple ranking as well as proportional piling. Data from KIIs and FGDs were analyzed using content analysis in NVivo (Version 12.0). The commonest livelihood activity was small-scale mixed farming. Most of the households kept dogs, but they are ranked at second-lowest in terms of economic value amongst all domestic animals. Free-roaming and tethering were the common dog-keeping systems, and home-based feed (food leftovers, bones) was provided mainly to the tethered dogs. Rabies, also locally known as “Eddalu Lyembwa” (that can be translated as "madness of the dogs"), was ranked as the disease of most importance amongst dogs, besides other common diseases like skin diseases, venereal diseases, worm infestations, and tick infestations. Inadequate vaccination services for both humans and dogs were reported, and dog bite victims traveled long distances to seek post-exposure prophylaxis after dog bites. It can be concluded that there is a clear request for periodic mass vaccination campaigns against rabies among dogs, and access to vaccines within reasonable distances by humans after rabies exposure, but also pre-emptive vaccination for those at high risk, such as veterinarians, needs to be improved. In addition, service-learning and community engagement through sensitization and outreach services addressing dog owners and general community is paramount. This could address issues related to proper dog management practices and health seeking behaviors in case of dog bites in order to greatly reduce the burden of rabies in the country.